Risk factors of respiratory syncytial virus infection among pediatric influenza‐like illness and severe acute respiratory infections in Suzhou, China. Issue 3 (9th November 2017) - Huang, Yukai; Hua, Jun; Wang, Dan; Chen, Liling; Zhang, Jun; Zhu, Hong; Tian, Jianmei; Zhang, Tao; Zhao, Genming
Abstract : The characteristics and risk factors of respiratory syncytial virus (RSV) infection among children has not yet been fully understood. To address the characteristics of RSV‐associated illness and risk factors of RSV infection among children under 5 years of age in Suzhou, China. From April 2011 to March 2014, we conducted a prospective surveillance among children in Suzhou, China. Nasal or throat swabs were collected from outpatients with influenza‐like illness (ILI) and inpatients with severe acute respiratory infections (SARI). RSV was detected by reverse‐transcriptase polymerase chain reaction and direct fluorescent antibody assay for children with ILI and SARI, respectively. Multivariable logistic‐regression models were constructed to explore risk factors and symptoms of RSV infection. Of 3267 ILI and 1838 SARI children enrolled in the study, 192 (5.9%) and 287 (15.6%) tested positive for RSV, respectively. Among ILI patients, children with RSV infections visited clinics more often ( P  = 0.005) and had longer duration of fever ( P  = 0.032) than those without RSV infection. All RSV‐positive children had an increased risk of having cough (OR = 2.9), rhinorrhea (OR = 1.6), breathing difficulty (OR = 3.4), wheezing (OR = 3.3), and irritability (OR = 2.7). Children aged <2 years, had history of prematurity (OR = 2.0) and recent respiratory infections (OR = 1.3) were more likely to get infected by RSV. Children with SARI had higher positive rate of RSV than those with ILI. Cough, rhinorrhea, and wheezing were the most common symptoms in RSV infection. Children aged <2 years, had history of prematurity and recent respiratory infections were the potential risk factors for RSV infection.